Electro-Mechanical Characterization of Graphite/Epoxy Composites as Potential External-Layer Material for Antenna Radome - Aruma, John; Njeri, Waweru; Muguro, Joseph (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2025)
Graphite is widely recognized in electrical applications for its inherent conductivity. As a reinforcement in composite materials, graphite fibers greatly improve both strength and rigidity, making them ideal for constructing radomes. Traditionally, radomes used in ground and naval settings are made from high-cost materials, such as fiberglass, quartz, and aramid fibers, which are often combined with resins like polyester and epoxy. Nonetheless, issues in structural formation continue to pose challenges. This study aims to investigate the electrical and mechanical properties of graphite/epoxy composites using a dynamic mechanical analyzer (DMA) in double cantilever mode, in accordance with ASTM D7028-07 standards. The objective is to prepare epoxy/graphite composites on a high-density polyethylene (HDPE) substrate with varying composition levels. The study further aims to evaluate the electrical and mechanical properties of electrostatic discharge (ESD) composites using the dynamic materials testing (DMT) method, with a focus on analyzing graphite-epoxy composites as an external layer on antenna radomes. Various specimen types—pure epoxy, surface-coated, and mixed samples with different graphite particle concentrations—were tested at temperatures from 0 to 140°C. A 30V voltage was applied to each specimen, and the resulting current and sheet resistivity were recorded. The electro-mechanical and viscoelastic properties were analyzed, revealing that stress-induced plastic flow occurred in some specimens, accompanied by increased strain energy in graphite-weighted samples. Surface-coated specimens demonstrated distinct behavior, while mixed samples showed a linear strain energy increase up until fracture. Conductivity in epoxy composites was affected by filler content, with conductivity improvements up to a certain filler percentage.